2013
DOI: 10.1007/s00403-013-1399-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between bullous pemphigoid and primary malignant cancers: an English national record linkage study, 1999–2011

Abstract: We conducted a nationwide record-linked study using all English NHS hospital admission data and mortality statistics from 1999 to 2011 to evaluate the risk of concurrent or subsequent bullous pemphigoid (BP) in a cohort of 2,873,720 individuals with malignant cancers, when compared with a reference cohort. We calculated standardised rate ratios (RRs) based on person-years at risk, comparing the observed and expected numbers of BP cases in the cancer cohort with those in the reference cohort. Overall, the cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 20 publications
2
44
1
4
Order By: Relevance
“…While studies initially reported an association between BP and cancer, 1 subsequent studies 4,5 have refuted this association, including a recent British study. 6 Although there is a possibility of increased risk of malignant neoplasm in younger patients with BP, 7 we did not find this association.…”
mentioning
confidence: 82%
“…While studies initially reported an association between BP and cancer, 1 subsequent studies 4,5 have refuted this association, including a recent British study. 6 Although there is a possibility of increased risk of malignant neoplasm in younger patients with BP, 7 we did not find this association.…”
mentioning
confidence: 82%
“…Since irradiated skin is reported to have increased vascular permeability [35], these autoantibodies may produce BP initially localized to the site of radiation. Additionally, studies have conclusively demonstrated that the correlation between BP and cancer is simply coincidental and not necessarily causative [46,47]. However, in these patients, the cancers were limited to the breast and BP occurred in the majority of cases at the sites of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a trial of a somatostatin analog, ocreotide, the rate of kidney volume increase was slowed compared with placebo, 32 and post hoc analyses suggested that octreotide may also reduce liver parenchyme and cyst expansion. 33 However, it also led to increased numbers of nonserious reports of gallstones (octreotide: ten of 40 3%]). The two reported serious cases of acute cholecystitis in this study were both among those allocated octreotide.…”
Section: Discussionmentioning
confidence: 99%
“…We used anonymized linked all England HES inpatient records with additional linkage to national mortality records. 40 Since 1998, HES have recorded information on all hospital inpatient activity in England, including dates of admission and discharge; demographics (including age, sex, and ethnicity); measures of social deprivation; the primary diagnostic reason for admission with relevant secondary diagnoses coded using the International Statistical Classification of Diseases and Related Health Problems Revision 10 (ICD-10) 41 ; and all procedures coded using the Office of Population Censuses and Surveys Classification of Surgical Operations and Procedures (OPCS), version 4.…”
Section: Disease Association Study Using All England Hospital Episodementioning
confidence: 99%